Angiotensin II analogs comprised of pro-amb (gamma-turn scaffold) as angiotensin II type 2 (AT(2)) receptor agonists - Jedhe, Ganesh S.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Pasha, Santosh; Sanjayan, Gangadhar J. (Chemical Communications, 2016)
We describe herein the design, synthesis and conformational investigation of Pro-Amb (proline-3-amino-2-methoxybenzoic acid) incorporated Angiotensin II and its truncated analogues. Solution-state NMR and CD studies suggest gamma-turn-like conformation in Pro-Amb analogs in aqueous solution. Furthermore, Pro-Amb analogs have been shown to act as AT(2) receptor agonists.